2020
DOI: 10.1177/2192568220975387
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Vertebral Body Sliding Osteotomy as a Surgical Strategy for the Treatment of Cervical Ossification of the Posterior Longitudinal Ligament

Abstract: Study Design: Retrospective cohort study. Objectives: Vertebral body sliding osteotomy (VBSO) has previously been reported as a technique to decompress ossification of the posterior longitudinal ligament (OPLL) by translating the vertebral body anteriorly. This study aimed to evaluate the radiological and clinical efficacies of VBSO and clarify the surgical indications of VBSO for treating myelopathy caused by OPLL. Methods: Ninety-seven patients with symptomatic OPLL-induced cervical myelopathy treated with V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 40 publications
0
30
1
Order By: Relevance
“…Although bone spurs and OPLL mass are not directly resected in VBSO but translated anteriorly, clinical outcomes were comparable to those of ACDF and ACCF. Therefore, the advantages of anterior decompression do not necessarily require direct removal of compressive lesions and can be achieved by canal widening through indirect decompression via anterior translation 14,15,17…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although bone spurs and OPLL mass are not directly resected in VBSO but translated anteriorly, clinical outcomes were comparable to those of ACDF and ACCF. Therefore, the advantages of anterior decompression do not necessarily require direct removal of compressive lesions and can be achieved by canal widening through indirect decompression via anterior translation 14,15,17…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated better lordosis restoration and faster bone union with VBSO than with corpectomy 16–18. Despite these favorable results, the longevity of VBSO has not been shown, as previous studies have been relegated to only short-term follow-up 14,17,19. Whether these favorable effects could be maintained over long-term surveillance or whether VBSO could result in unexpected complications, remains unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…VBSO is a surgical technique reported as a substitute for corpectomy [ 10 ]. In VBSO, the vertebral body is translated anteriorly to widen the spinal canal, minimizing the need for direct removal of the pathology such as ossified mass and bony spurs [ 11 - 13 ]. For double transverse incision, 2 transverse incisions were made parallel to Langer’s skin line, with the bridge of the minimum 3-cm flap secured between the 2 incisions ( Fig.…”
Section: Methodsmentioning
confidence: 99%